EUReCA: An open-source urban building energy modelling tool for the efficient evaluation of cities energy demand. (August 2021) - Prataviera, Enrico; Romano, Pierdonato; Carnieletto, Laura; Pirotti, Francesco; Vivian, Jacopo; Zarrella, Angelo
Abstract: Recently, the attention towards Urban Building Energy Modelling has been growing due to the large contribution of cities on the worldwide energy consumption rate. In fact, many models have been developed to simulate buildings and urban energy systems. This article presents a new open-source tool for city-scale simulations. The platform implements the electrical analogy to model buildings thermal behaviour through resistance-capacitance networks, thus predicting the energy demand of urban areas with a bottom-up approach and low computational resources. The model has been applied to two urban areas: a small and well-known neighbourhood and a broader urban district. Results show the accordance of simplified models with respect to single building detailed simulations in the evaluation of the seasonal energy demand. When comparing results at hourly resolution, the accuracy is increased by considering a thermal network that splits buildings' surfaces into two capacitances. A model based on a single capacitance leads to a higher deviation, especially on the daily peak power. Regarding the district simulation, these simplified networks show a good prediction of the buildings energy demand according to relevant European references, thus demonstrating the reliability of the proposed approach despite their low computational effort. Highlights: EUReCA, an UBEM platform based on lumped-capacitance building models is presented. EUReCA handles both 2D shapefiles and 3D CityJSON georeferenced data. A restricted well-known neighbourhood and a wider city district are analyzed. A two-capacitances building model enhances power peak and load profile prediction. Aggregated results at district level demonstrate EUReCA's reliability.